"What a cool facility!!! " - but how do the inhabitants feel? (Journal of Laboratory Animal Science, 2022)
“22±2°C” is a figure imprinted hard and deep into the brain  of any facility manager since the very early days of his/her  career. The value which got imbibed globally, without much  ruckus is however, now a “hot” topic after which scientists and  veterinarians in the field of basic laboratory animal science are  in hot-trail of. Mice are housed in laboratories at 20–24°C, which is way  below their lower critical temperature which is approximately  30°C where the range of their thermoneutral zone (TNZ) is  from 26°C-34°C. Hence, housing these animals at lower  temperature ranges will increase the thermal stress and has the  potential to alter scientific outcomes (Gaskill BN et al., 2012).  This is true for rats as well which are housed at 22-24°C;  evidently below their lower critical temperature of 26°C.  TNZ of pigs weighing from 1 kg to 5 kg on a maintenance  diet, housed in groups of 10 pigs per pen, on concrete floor,  is 22-32°C and for 40Kg weighing pigs in similar conditions  as stated above but for 15 pigs housed per pen is 13-26°C.  In simpler terms, the thermal comfort zone of pigs in their  various stages of production are 10-21°C or a mature boar,  lactating sow and a gestating sow; 24-30°C for a weaner and  32-38°C for a new-born piglet (for which heating up has to be  provided) (Stewart and Cabezón, 2016).
Keywords: thermal comfort; CPCSEA; hamster